Problematika Perkawinan Beda Agama Dalam Konteks Hukum Islam dan Solusinya - Onytra Nirwana Prihatin; Khalimi; Muhammad Faozan (TAFAQQUH, 2022)
This study aims to examine the phenomenon of interfaith marriages in Indonesia, focusing on diverse legal interpretations and solutions to the legal issues arising from the implementation of interfaith marriages within the context of Law Number 1 of 1974 on Marriage. The research employs a qualitative approach with document analysis as the primary method. Data are collected from legal literature, religious interpretations, and court rulings related to interfaith marriages. The data analysis technique involves an in-depth review of legal texts and the various interpretations from experts. The findings show significant differences in the interpretation of Article 2, paragraph (1) of Law Number 1 of 1974 regarding the validity of marriages according to respective religious laws. Although the law does not explicitly prohibit or permit interfaith marriages, interpretations from several legal experts and court rulings reflect diverse viewpoints. Case examples, such as the Surabaya District Court Decision Number 916/Pdt.P/2022/PN Sby, which granted the application for an interfaith marriage, illustrate the inconsistency between religious and civil law. This study contributes to a deeper understanding of the complexities of interfaith marriage law in Indonesia. The research findings also offer legal solutions that can be considered in the formulation of more comprehensive and equitable legislation regarding interfaith marriages. Thus, it is hoped that there will be synergy between religious law and state law in addressing the issues of interfaith marriages and providing clear legal protection for couples who choose this path